CHANGE OF SANDSTONES UNDER THE INFLUENCE OF IRRIGATION (Scientific journal of the Fergana State University, 2025)
Today, the world population's need for food products is increasing. The limitation of arable land, acceleration of degradation processes directly causes problems in food production. Efficient use of available resources is one of the important tasks facing agriculture. The article briefly covers the issues of changes in sand dunes of Central Fergana under the influence of irrigation.